2008
DOI: 10.1002/path.2476
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of CNS‐draining lymph nodes reduces relapse severity in chronic‐relapsing experimental autoimmune encephalomyelitis

Abstract: Despite lack of classical lymphatic vessels in the central nervous system (CNS), cells and antigens do reach the CNS-draining lymph nodes. These lymph nodes are specialized to mediate mucosal immune tolerance, but can also generate T- and B-cell immunity. Their role in multiple sclerosis and experimental autoimmune encephalomyelitis (EAE) therefore remains elusive. We hypothesized that drainage of CNS antigens to the CNS-draining lymph nodes is vital for the recurrent episodes of CNS inflammation. To test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 53 publications
4
90
0
Order By: Relevance
“…Because LTis are important for lymph node development, RorcÀ/À mice lack these secondary lymphoid organs raising the possibility that Th17 cell induction is compromised in these mice. However, although one study showed slight diminution of disease during relapse after surgical excision of CNS draining lymph nodes [68], most data indicates that lymph nodes are dispensable for cell mediated immunity in EAE and only necessary for antibody affinity maturation and class switching [7,27,28]. Due to the normal splenic architecture of RorcÀ/À mice and our observation of normal cell proliferation and cytokine production of transferred T cells in these mice (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Because LTis are important for lymph node development, RorcÀ/À mice lack these secondary lymphoid organs raising the possibility that Th17 cell induction is compromised in these mice. However, although one study showed slight diminution of disease during relapse after surgical excision of CNS draining lymph nodes [68], most data indicates that lymph nodes are dispensable for cell mediated immunity in EAE and only necessary for antibody affinity maturation and class switching [7,27,28]. Due to the normal splenic architecture of RorcÀ/À mice and our observation of normal cell proliferation and cytokine production of transferred T cells in these mice (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The nominal myelin antigen, MOG, might be available to the MOG-specific B cells in the local draining LNs through specialised transport via lymphatic vessels. Indeed, deposits of myelin antigen were detected in the brain-draining cLNs during active EAE and surgical removal of these LNs ameliorated the severity of EAE [28,123]. Detailed analysis of the cLNs in RR mice found evidence of changes which preceded the onset of spontaneous EAE.…”
Section: Gut Microbiota In Ms and Its Animal Modelsmentioning
confidence: 95%
“…As discussed above, this connection is primarily due to the glymphatic system that connects ISF and CSF (15). In both rodent and primate models of multiple sclerosis, for example, brain antigens were increased in the cervical lymph nodes (80,81). After stroke, brain injury, or oligodendrocyte death induced by diphtheria toxin, myelin antigens have similarly been found to accumulate in the cervical lymph nodes (82)(83)(84).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 96%